2012
DOI: 10.1039/c2cp40764g
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of heterogeneous molybdate and chromate phase assemblages in model nuclear waste glasses by multinuclear magnetic resonance spectroscopy

Abstract: A series of sodium borosilicate glasses containing cesium, molybdenum, and chromium was prepared to investigate the partitioning of chromium amongst the glass and phase-separated crystalline molybdates. The precipitates were examined by (133)Cs, (23)Na, and (95)Mo MAS NMR, revealing a phase assemblage consisting of Na(2)MoO(4), Na(2)MoO(4)·2H(2)O, Cs(2)MoO(4), Cs(2)CrO(4), CsNaMoO(4)·2H(2)O, and Cs(3)Na(MoO(4))(2). (133)Cs MAS NMR indicates random substitution of Cr into the Mo sites of Cs(3)Na(MoO(4))(2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…The site‐specific nature of high‐resolution NMR provides additional information about the identities of the devitrification products formed with different Mo‐loading levels and quench rates. With reference to peak assignments drawn from previous work, the 133 Cs MAS NMR data reveal that the dominant phases are CsNaMoO 4 ·2H 2 O (−70 ppm), Cs 3 Na(MoO 4 ) 2 (161, −144 ppm), and Cs 2 Mo 2 O 7 (22, 9, −14, −56 ppm), with several unidentified peaks (69, 47, −9, −78 ppm) which may belong to Cs molybdate phase(s) not yet characterized. CsNaMoO 4 ·2H 2 O is the most populous compound appearing in the 133 Cs MAS NMR spectra and is prominent also in the 23 Na MAS NMR data (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The site‐specific nature of high‐resolution NMR provides additional information about the identities of the devitrification products formed with different Mo‐loading levels and quench rates. With reference to peak assignments drawn from previous work, the 133 Cs MAS NMR data reveal that the dominant phases are CsNaMoO 4 ·2H 2 O (−70 ppm), Cs 3 Na(MoO 4 ) 2 (161, −144 ppm), and Cs 2 Mo 2 O 7 (22, 9, −14, −56 ppm), with several unidentified peaks (69, 47, −9, −78 ppm) which may belong to Cs molybdate phase(s) not yet characterized. CsNaMoO 4 ·2H 2 O is the most populous compound appearing in the 133 Cs MAS NMR spectra and is prominent also in the 23 Na MAS NMR data (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…This water-soluble phase can contain radionuclides such as 137 Cs/ 135 Cs and 90 Sr, which can be partitioned to the molten molybdate/ chromate/sulfate/chloride salt ("yellow phase"). 40,[42][43][44] Extended X-ray absorption fine structure spectroscopy (EXAFS) has suggested that Mo in borosilicate glass forms MoO 2À 4 tetrahedra that are unconnected with the borosilicate network but rather associated with alkali and alkaline earth regions. 45 Others have suggested that MoO 3 , at least at increasing concentrations, acts as a "reticulating agent" for the silicate network where Q 4 units are increased, and the molybdate exists in a "depolymerized region" rich in alkali and alkaline earth ions and nonbridging oxygens.…”
Section: Comparison Of Perrhenate Sulfate and Molybdate In Borosilimentioning
confidence: 99%
“…We have previously used various solid-state NMR techniques to detect devitrification [38][39][40] and glass-in-glass phase separation [33] in model cesium-and molybdenum-containing nuclear waste glasses.…”
Section: Introductionmentioning
confidence: 99%